Pengaruh Kompensasi Dan Pengembangan Karir Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Moderating( Studi Empiris pada DPPKAD Kabupaten Boyolali ) - Pratiwi, Desti Iindh Eka; , Drs. Wahyono, MA, Ak (2015)
The purpose of this study was to analyze the effect of compensation and career development on employee performance and motivation to work as a moderating variable in DPPKAD Boyolali. This research used a sample of 80 employees. The sampling method using convenience sampling method that is where the sampling is done from the employees are easy to find and are willing to become respondents. Data analysis tool used in the research are moderating regression analysis (MRA). These results indicate that 1) the compensation significant effect on the performance of employees, 2) career development does not effect the performance of the employee, 3) motivation to work do not effect the performance of the employee, 4) compensation with the motivation to work as a moderating variable does not effect the performance of the employee, 4) career development and motivation to work as a moderating variable is not effect the performance of the employee.